Monogamy As The Substance of Pre-Nuptial Agreement: A Cross-Mazhab Comparative Study - Adib, Ahmad Hidhir; Ahmad, Moch Said (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
Polygamy is one of the factors causing divorce. To overcome this, the concept of a pre-nuptial agreement can be applied as proposed by Sayyidah Sukainah towards her husband. This study aims to answer the legality of monogamy requirements proposed by the bride. The research method used in this research is literature study with a mazhab (school of thought) comparative approach. The author will compare the views of 5 mazhab; Hanafi, Maliki, Shafi'i, Hambali and Dzahiri.The results of this study indicate that if a woman who adheres to the mazhab of Syafi'i or Maliki does not want her husband to be polygamous, then make a nazar (vow) to her husband. Meanwhile, if she belongs to the Hambali, the scholars legalize this monogamy requirement, even if it has become a tradition in the woman's region, then the condition is automatically binding. Whereas in the Hanafi mazhab, these conditions are not binding, but have an impact on the type of Mahar (dower). So in case of the husband does not meet these requirements, then the wife is entitled to a mahar mitsil dowry of mahar mitsil (determined dower). Whereas in the Dzahiri mazhab, these conditions are not binding, even in case they appear in the contract, it results in the cancellation of the marriage.